Pro-Rich Inflation and Optimal Income Taxation - Eren Gürer; Alfons Weichenrieder (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper studies the implications of an increase in the price of necessities, which disproportionally hurts the poor, for optimal income taxation. Our analyses show that, when the government is utilitarian and disutility from labor supply is linear, the optimal net nominal tax schedule is unchanged and the government expects households to supply more labor in order to secure their consumption expenditures. Quantitative analyses with convex disutility of labor supply reveal that, because of positive labor supply effects, keeping average tax rates constant suffices to optimally react to the asymmetric price shock. However, the poorest agents are expected to increase their labor supply the most. Thus, optimal income tax policy in response to asymmetric price changes does not prevent the disproportional decline in the indirect utility of poorer households.
Keywords: H21; E31; 330; pro-rich inflation; optimal income taxation